Variation of gut microbiota composition in a honey bee breeding population: exploring potential links with docility and honey production - M.G. De Iorio; G. Minozzi; F. Tiezzi (Animal)
The current global decline of bee populations is of great concern due to their crucial role as pollinators and for the conservation of biodiversity. Today the survival of bees is increasingly dependent on beekeeping practices. In this context, the present study explores the composition of honey bee gut microbiota, its changes in time and its potential relationship with two key traits of interest to beekeepers: docility and honey yield. In this study, 77 colonies, belonging to a breeding population selected for these phenotypes, were sampled three times over a 5-month period, leading to a total of 190 samples. Results showed that Apis mellifera, differently from other insects, hosts a specialised gut microbial community composed of five ever-present bacterial taxa. However, the proportional abundance of these bacterial taxa undergoes significant seasonal shifts, reflecting seasonal changes in diet. Moreover, the association between the composition of the honey bee microbiota and honey production was identified. In conclusion, this study offers insights into the composition and the seasonal dynamics of honey bee gut microbiota.